2016
DOI: 10.1038/srep37690
|View full text |Cite
|
Sign up to set email alerts
|

Highly expressed ribosomal protein L34 indicates poor prognosis in osteosarcoma and its knockdown suppresses osteosarcoma proliferation probably through translational control

Abstract: Osteosarcoma has devastating health implications on children and adolescents. However, due to its low incidence and high tumor heterogeneity, it is hard to achieve any further improvements in therapy and overall survival. Ribosomal protein L34 (RPL34) has been increasingly recognized to promote the proliferation of malignant cells, but its role in osteosarcoma has not been investigated. In this study, real-time quantitative PCR (RT-qPCR) and immunohistochemistry revealed that RPL34 was highly expressed in oste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
29
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 60 publications
(64 reference statements)
3
29
0
Order By: Relevance
“…In order to define the role of RPL34 in AML, we constructed shRPL34-lentivirus to successfully knockdown RPL34 in HL-60 cell line, a commonly used AML cell line. Consistent with other studies performed in solid tumors [8][9], we found knockdown of RPL34 could significantly inhibit cell proliferation and trigger apoptosis. In cell cycle distribution analysis, more HL-60 cells transfected with shRPL34 lentivirus were arrested in S phase.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In order to define the role of RPL34 in AML, we constructed shRPL34-lentivirus to successfully knockdown RPL34 in HL-60 cell line, a commonly used AML cell line. Consistent with other studies performed in solid tumors [8][9], we found knockdown of RPL34 could significantly inhibit cell proliferation and trigger apoptosis. In cell cycle distribution analysis, more HL-60 cells transfected with shRPL34 lentivirus were arrested in S phase.…”
Section: Discussionsupporting
confidence: 92%
“…Ribosomal proteins (RPs) play important roles in cell proliferation and growth in most eukaryotic cells [7]. However, in recent years, increasing evidence has shown RPs may involve in the process of tumorigenesis, metastasis, and therapy resistance [7,[9][10][11] have been reported to reveal the role of RPL34, one type of ribosomal protein, in solid tumors [8][9]. To the best of our knowledge, the present study is the first to investigate the expression and clinical significance of RPL34 in AML.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ajiro et al found that serine/arginine-rich splicing factor 3 (SRSF3) regulates the expression of DDX5 in human OS U2OS cells [ 30 ]. By participating in the transcriptional regulation of ribosomal protein L34 (RPL34) which plays an important role in the proliferation of OS cells, MYC interacts with the subunits of EIF3 and probably involves the translational control of growth-promoting proteins [ 31 ]. EIF3, a multi-subunit complex, plays a critical role in translation initiation.…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, RPL34 overexpression in osteosarcoma promotes proliferation of malignant cells. In this case, RPL34, whose transcription is regulated by c-Myc, cooperates with certain subunits of the important initiating translation factor (eIF3) which probably results in increased protein biosynthesis, including those promoting growth (Luo et al 2016 ). In the pancreatic cancer (PC) cells, RPL34 is hyperexpressed most probably through hypomethylation of the promoter of a gene encoding this protein.…”
Section: A Nucleolus As a Support Of Cancer Cellsmentioning
confidence: 99%